A randomized multicenter study comparing seawater washes and carmellose artificial tears eyedrops in the treatment of dry eye syndrome - Diaz-Llopis M (Dove Medical Press, 2019)
Manuel Diaz-Llopis,1–5 Maria Dolores Pinazo-Duran,2,3,6–9 Loreto Diaz-Guiñon,5 Miriam Rahhal-Ortuño,10 Mercedes Perez-Ramos,8,9 Rosabel Bosch,8,9 Roberto Gallego-Pinazo,11,12 Rosa Dolz-Marco,11,12 Teresa Diaz-Guiñon,5 María Diaz,1,5 Francisco Javier Romero,13 Angel Cisneros10 1University of Valencia, Valencia, Spain; 2Ophthalmology Unit, Faculty of Medicine, University of Valencia, Valencia, Spain; 3Molecular Ophthalmology Unit, Faculty of Medicine, University of Valencia, Valencia, Spain; 4Consellería de Sanitat (Valencian Regional Health Ministry), Valencian Autonomous Government, Valencia, Spain; 5IOVA – Valencia Ophthalmology Institute, Valencia, Spain; 6Hospital Universitario Doctor Peset, Valencia, Spain; 7Santiago Grisolía Eye Research Laboratory, FISABIO, Valencia, Spain; 8Specialised Medical Centre Alboraya, Valencia, Spain; 9Specialised Medical Centre Monteolivete, Valencia, Spain; 10Department of Ophthalmology, La Fe Hospital, Valencia, Spain; 11IMED Hospital, Valencia, Spain; 12Oftalvist Clinic, Valencia, Spain; 13European University of Valencia, Valencia, Spain Purpose: To investigate the safety and efficacy of sterile isotonic seawater washes vs standard treatment with carmellose artificial tears in dry eye syndrome (DES). Patients and methods: This is a randomized multicenter prospective study with 12 weeks of follow-up. A group of patients with DES (N=60) were treated with seawater spray (Quinton®) five times daily, and another similar group (N=60) were treated with carmellose artificial tears eyedrops (Viscofresh® 0.5%) five times a day. The parameters studied and measured were as follows: Ocular Surface Disease Index questionnaire score, Schirmer I test (without anesthesia) score, tear osmolarity (TearLab®), tear breakup time, tear meniscus height (meniscography OCT), fluorescein corneal staining score (National Eye Institute scale), lissamine green conjunctival staining score, and levels of IL-1 beta and IL-6 in tears (Luminex® 200). Results: In the group treated with seawater, symptoms decreased by 68%, and the decrease was 26% statistically superior to the group treated with carmellose artificial tears eyedrops (P<0.001). Levels of IL-1 beta and IL-6 in tears significantly decreased in the seawater group compared to the carmellose artificial tears group (19%/17% vs 52%/51%) (P<0.001). There were no statistically significant differences in the other measured parameters. There were no cases of poor tolerance or side effects. Conclusion: Administration of seawater is more effective than treatment with carmellose artificial tears in reducing symptoms and pro-inflammatory molecules (IL-1 beta and IL-6) in tears of patients with DES. Keywords: dry eye syndrome, isotonic seawater, artificial tears, carmellose, IL-1 beta, IL-6, quality of life